Marital Maintenance Neglect and Divorce Dynamics: An Empirical Socio-Legal Study in Gampong Neuheun, Aceh Besar - Inayatul Fitri; Zaiyad Zubaidi; Muhammad Husnul; Bilaly Sangare; Isa Olawale Solahudeen (An-Nisa: Journal of Islamic Family Law, 2026)
Neglect of maintenance by the husband is one of the dominant factors that cause divorce which is not always related to structural poverty, but also to unproductive behavior and intentional neglect in fulfilling household economic obligations. This study aims to analyze the social dynamics of maintenance negligence, identify the main causative factors, examine its impact on family stability, and evaluate the effectiveness of custom-based mediation mechanisms in conflict resolution in Gampong Neuheun, Mesjid Raya District, Aceh Besar Regency. This study uses a qualitative approach with the type of field research. Data was collected through in-depth interviews with gampong officials, traditional leaders, and religious leaders, and strengthened by participatory observation and documentation studies. The results of the study show that livelihood instability is more predominantly caused by laziness, the involvement of the husband in online gambling, and dependence on social assistance that is not managed productively, thus triggering prolonged conflicts and increasing the risk of divorce. Customary mediation has been proven to play a role in reducing conflicts in the early stages, but its effectiveness is limited when it is not accompanied by a commitment to behavior change from the husband. This study recommends strengthening community-based regulations and supervision as well as family economic empowerment programs that are integrated with customary mediation mechanisms as preventive measures to reduce the divorce rate due to neglect of alimony.